Relationship between Online Registration Service Quality and Outpatient Satisfaction - Tinarbudi Gavinov, Ivan; Anggriani, Fenny (IJBLE Scientific Publications Community Inc., 2023)
The development of various technologies provides convenience in the health sector, one of which is online registration which aims to reduce the accumulation of patients due to long registration times. Analysis of the application of a system is carried out so that the achievement of the implementation of an information system can be known and further action can be planned to improve the performance of its implementation. The purpose of this study was to describe the application of an online outpatient registration system. This type of research is quantitative descriptive using a cross sectional approach. which was held at RSU Rajawali Citra Yogyakarta from January 2022 – March 2022. The sample of this study amounted to 95 respondents with a sampling technique that is purposive sampling. Data analysis using Kendal tau. Test. The results of the Kendal tau test analysis obtained tangible values ​​with satisfaction obtained a significance value of p = 0.000, reliability with satisfaction obtained a significance value of p = 0.000, responsiveness with satisfaction obtained a significance value of p = 0.000, assurance with satisfaction obtained a significance value of p = 0.000, and empathy with satisfaction obtained a significance value of p = 0.000.